Identidad y política en la música del cine chileno (1939-1973) - Farías, Martin (Ariadna Ediciones, 2021)
This book analyzes the uses of music in the cinema in Chile in terms of meaning and interpretation, considering the socio-political circumstances that have marked the country during the 20th century. The time frame of this research ranges from 1939 when the sustained production of films with optical sound was established in the country and 1973, when the civil-military coup d'état destroyed all the pillars of the cultural field in Chile and many filmmakers and composers left for the exile. This work aims to challenge existing historiography and research by emphasizing the sound dimension of Chilean cinema. Far from being a secondary and decorative aspect, music has been a central element in different moments and practices of Chilean cinema both internally in its formal and narrative proposals and externally in its discursiveness and links with the social and political.